Investigation of Fertilizing Capacity of Zebrafish () Sperm Exposed to Heavy Metals - Flóra Kerekes; Tímea Kollár; Gyöngyi Gazsi; Eszter Kása; Béla Urbányi; Zsolt Csenki-Bakos; Ákos Horváth (SAGE Publishing, 2020)
The objective of our study was to investigate the effects of heavy metals on the fertilizing capacity of exposed zebrafish sperm, on embryonic survival, and on occurrence of embryonic deformities following fertilization with exposed sperm. It is important to test heavy metals because they are well-known pollutants. Sperm of externally fertilizing species can get in contact with pollutants found in aquatic environment. Zebrafish sperm, despite its advantages, has seldom been used in in vitro toxicological studies and no reports are available regarding the fertilizing capacity of exposed sperm. Zebrafish sperm was stripped and exposed to concentrations of the tested heavy metals (Zn 2+ , Cd 2+ , Cr 3+ , Cu 2+ , Ni 2+ , Hg 2+ , As 3+ ) for 30 or 120 minutes. Calculated half-maximal effective concentration (EC 50 ) values do not differ significantly from those calculated for motility for any of the tested heavy metals, which means fertilization rate can indicate the toxicity of the given substance following exposure of sperm. Thus, its application as in vitro toxicological end point is reasonable. The survival of embryos and embryonic development have not been affected by the exposure of spermatozoa, which means all alterations in spermatozoa caused by heavy metals have been expressed before 24 hours post fertilization.